Pengembengan Media pembelajaran Card Match Circle Pada Mata Pelajaran Ilmu Pengetahuan Sosial Kelas VII Di MTs Ma’arif Ambulu Jember Tahun Pelajaran 2024/2025: Pengembengan Media pembelajaran Card Match Circle Pada Mata Pelajaran Ilmu Pengetahuan Sosial Kelas VII Di MTs Ma’arif Ambulu Jember Tahun Pelajaran 2024/2025 - Najilah, Lailatul; Islami, Novita Nurul (Jurnal Penelitian dan Pendidikan IPS, 2025)
This study aims to develop interactive learning media based on Card Match Circle (CMC) to improve student learning outcomes in Social Sciences (IPS) subjects in class VII MTs Ma'arif Ambulu Jember, especially the material on Social and Cultural Diversity of Society. The background of this study is the low interest in learning and achievement of student learning outcomes that have not met the Minimum Completion Criteria (KKM), due to monotonous learning methods and the lack of interesting media. The study used the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The products developed were CMC media with colored cards and interactive spin-based games. The validation results showed that this media was very valid, with a score of 96% from media experts, 80% from material experts, and 86.6% from language experts. The practicality of the media was assessed as very good based on student responses. The effectiveness of the media was shown by an increase in students' pretest and posttest scores, both on a small scale (85% to 92%) and a large scale (80% to 90%). Thus, CMC media is proven to be valid, practical, and effective in improving students' social studies learning outcomes.